Knowledge, attitudes, practices, and beliefs regarding prenatal alcohol consumption among women in Leyte, the Philippines - Alice M. Huang; Matthew N. Neale; Spencer C. Darveau; Marianne J. Sagliba; Amabelle J. Moreno; Maria Paz G. Urbina; Veronica Tallo; Emily A. McDonald; Emily A. McDonald; Mario A. Jiz; Jennifer F. Friedman; Jennifer F. Friedman (Frontiers Media S.A., 2023)
ObjectivesFetal alcohol spectrum disorder (FASD) captures the broad range of emotional, cognitive, behavioral, and congenital abnormalities associated with maternal alcohol consumption, and women living in resource-limited settings may be higher risk. This study aims to examine knowledge, attitudes, practices, and beliefs (KAPB) of women in Leyte, The Philippines regarding prenatal alcohol consumption.MethodsOne hundred postpartum women were recruited from a birth cohort in Leyte. A prenatal alcohol use KAPB survey was constructed in Waray, the local language. The survey was administered in June-September 2019. Descriptive statistics, chi-squared test, and Fisher's exact test were used to analyze responses.ResultsSeventy-five percent of subjects reported drinking tuba, a local palm wine, during pregnancy. Most participants (75%) did not believe tuba contained alcohol. Women who believed tuba contains no alcohol were more likely to drink tuba during pregnancy (81.3%) than women who believed tuba contains alcohol (56.0%), X2(1, N = 100) = 6.41, p = .011. Women who drank tuba during pregnancy were more likely to believe tuba has health benefits (60%) than women who did not drink tuba during pregnancy (12%), Fisher's exact p < .05, citing increased red blood cell count and unproven antiparasitic qualities. Fifteen percent of subjects reported having fed their babies tuba. Nearly all (98%) were willing to attenuate tuba/alcohol consumption if told that this practice negatively impacts pregnancies.ConclusionMisinformation about tuba appears widespread in Leyte. Educating women of reproductive age in Leyte regarding prenatal tuba use may lead to a reduction in tuba use.